การสร้างชีวิตที่สองในเกมออนไลน์: กรณีศึกษาชุมชนของ ผู้เล่นในญี่ปุ่นหลัง ค.ศ.2000 - ฤกษ์ดี มโนวชิรสรรค์ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Nowadays Japaneses people concern and suffering in daily life. Some of them choose the online game as the second life. Since 2000 A.D., The gaming technology had developed greatly. The community of gamers has been growing up with some influence from the game company. The purpose of this independent study is to research about the emergence of the second life due to the factors with presented beforehand via documents, websites, web-boards and social networks (SNS). This research shows that the community grows a number up by the influence of the internet and the development of technology that makes people who never know each other before playing games together. These activities form the bond between people. For example, the game Final Fantasy XIV presents the set of in-game activities that resemble the real life experience. The gaming company are the one who patch these two worlds, the gaming world and the real world, together. In social side, due to the pressure, inequalities and the hardness of living the real society. The adolescence choose the game as the escape since the game let them be what they want to be. This independent study makes us understand more in the second life and the uncertain relationships between them since it’s in the internet, there are more possibilities for the relationships. The gaming company patches these two worlds together.